Novel definition of the synergistic effect between carbon nanotubes and carbon black for electrical conductivity - Qu, Muchao; Nilsson, Fritjof; Schubert, Dirk W. (Nanotechnology, 2019)
Anisotropic ternary composites comprising poly(methy-methacrylate) (PMMA), carbon black (CB), and carbon nanotubes (CNTs) were extruded using a capillary rheometer and the electrical conductivities of the composites were measured and presented in a detailed contour plot covering a large range of filler fractions (up to 30 vol% CNTs, 20 vol% CB). A recent generic conductivity model for ternary composites was successfully validated using the conductivity measurements. When analyzing the conductivity measurements using four traditional definitions of 'synergy' between two conductive fillers, no clear synergetic effect was observed between CB and CNT. Also, when all the conductivity data for ternary CNT/CB composites from the existing literature was carefully gathered and analyzed, the number of confirmed occurrences of strong and convincing CNT/CB synergies was surprisingly low. Finally, a novel definition of synergy based on the physical aspect, in particular, its maximum, the 'synergasm', was defined in order to obtain a more precise instrument for revealing regions of potential synergy.
CRIS-Team WoS Importer:2019-04-12